Frequency of Hypothyroidism in Patients with Fibromyalgia Syndrome. - Naji, Ragad I.; Turki, Kismat M.; Al-Osami, Mohammad H. (Journal of the Faculty of Medicine Baghdad, 2013)
Background: Fibromyalgia (FMS) is characterized by chronic widespread pain and allodynia (pain from stimuli which are not normally painful with pain that may occur other than in the area stimulated) of more than 3 months duration. The current hypothesis of the etiology of FMS includes inflammatory and neuroendocrine disorders. Many features of fibromyalgia and hypothyroidism are virtually the same, and thyroid hormone treatment trials have reduced or eliminated fibromyalgia symptoms. These findings led the authors to test the hypothesis that fibromyalgia patients are hypometabolic compared to matched control .Patients and Methods: The samples  were taken from the patients attending the out-patient clinic in Medical city-  Baghdad Teaching Hospital – Rheumatology and Rehabilitation Consultation Unit , where the anthropometric tests were performed , from the period Nov. 2010 till June 2011The samples were taken from 57 fibromyalgia patients and 34 apparently healthy controls . Blood samples were collected and T3 , T4 , and TSH were estimated in serum of patients and control .Results: The present results show that only 6.6% of the FMS patients had elevated serum TSH level , and the T3 , T4 , and TSH results were non-significant .Conclusion: There is no conclusive evidence of specific thyroid dysfunction in FMS , although , it remains an important diagnosis to exclude when making a primary diagnosis .